2020
DOI: 10.1038/s41467-020-18485-7
|View full text |Cite
|
Sign up to set email alerts
|

Organic-to-inorganic structural chirality transfer in a 2D hybrid perovskite and impact on Rashba-Dresselhaus spin-orbit coupling

Abstract: Translation of chirality and asymmetry across structural motifs and length scales plays a fundamental role in nature, enabling unique functionalities in contexts ranging from biological systems to synthetic materials. Here, we introduce a structural chirality transfer across the organic–inorganic interface in two-dimensional hybrid perovskites using appropriate chiral organic cations. The preferred molecular configuration of the chiral spacer cations, R-(+)- or S-(−)-1-(1-naphthyl)ethylammonium and their asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
310
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 294 publications
(359 citation statements)
references
References 79 publications
13
310
0
Order By: Relevance
“…Importantly, our calculations indicated that the orbitals of the chiral carbons could not be coupled with those of copper or chlorine due to the long N−H⋅⋅⋅Cl and C−H⋅⋅⋅π hydrogen bonding. From the perspective of quantum theory, the chirality of the hybrid copper halides was a consequence of their chiral crystal structure ( C 2 space group), which can be described as [25] truenormalCnormalDboldR=Im{}μboldm …”
Section: Figurementioning
confidence: 99%
“…Importantly, our calculations indicated that the orbitals of the chiral carbons could not be coupled with those of copper or chlorine due to the long N−H⋅⋅⋅Cl and C−H⋅⋅⋅π hydrogen bonding. From the perspective of quantum theory, the chirality of the hybrid copper halides was a consequence of their chiral crystal structure ( C 2 space group), which can be described as [25] truenormalCnormalDboldR=Im{}μboldm …”
Section: Figurementioning
confidence: 99%
“…Importantly, our calculations indicated that the orbitals of the chiral carbons could not be coupled with those of copper or chlorine due to the long N−H⋅⋅⋅Cl and C−H⋅⋅⋅π hydrogen bonding. From the perspective of quantum theory, the chirality of the hybrid copper halides was a consequence of their chiral crystal structure ( C 2 space group), which can be described as [25] truenormalCnormalDboldR=Im{}μboldm …”
Section: Figurementioning
confidence: 99%
“…A handful of papers have already demonstrated their potential: enhanced spin transport and spin-exciton formation without an external magnetic field. [204][205][206][207] Last, this perspective describes the potentials and the issues of two different family of semiconductors: organics and halide perovskites. From the properties outlined above emerges their complementary nature.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A handful of papers have already demonstrated their potential: enhanced spin transport and spin‐exciton formation without an external magnetic field. [ 204–207 ]…”
Section: Discussion and Outlookmentioning
confidence: 99%